Keep Your Eye on the Ball; the Impact of an Anticipatory Fixation During Successful and Unsuccessful Soccer Penalty Kicks - Timmis, Matthew A.; Piras, Alessandro; van Paridon, Kjell N. (Frontiers in Psychology, 2018)
The success of a sporting task requiring an object to be kicked or hit towards a target (e.g. kicking a ball into a goal) is impacted by the length of the Quiet Eye (QE). Limitations in the ocular motor system mean that after impact, these fast moving objects are not tracked using smooth pursuit eye movements. Rather, anticipatory fixations are used to re-fixate ahead of the moving object. Using a soccer penalty kick, the current study investigated whether striking a stationary object to generate high ball velocity results in an anticipatory fixation prior to ball contact and if this occurs at detriment to the QE period and task success. Facing a goalkeeper, 12 participants produced a successful (scored) and unsuccessful (saved) penalty whilst wearing a mobile eye tracker. QE was longer in the successful compared to unsuccessful penalty (p=.036) and was due to QE offset ending later in the successful compared to unsuccessful penalty (p=.008). An anticipatory fixation occurred later (p=.025) and was shorter (p=.005) in successful compared to unsuccessful penalties. The football was kicked wider (more accurately) within the goal during the successful compared to unsuccessful penalty (p<.001). Results highlight the importance of the QE period in successfully executing a soccer penalty kick. Unsuccessful penalties were associated with shorter QE length and earlier QE offset, which was due to initiating an anticipatory fixation in prediction of tracking the fast moving football, resulting in kicking the ball more centrally in the goal, making it easier for the goalkeeper to save.